A comparison of Japanese and Australian consumers' sensory perceptions of beef. (17th June 2013) - Polkinghorne, Rod J.; Nishimura, Takanori; Neath, Kate E.; Watson, Ray
Abstract This paper presents a comparison of Japanese and Australian consumer sensory responses to beef, based on Meat Standards Australia methodology. Japanese and Australian consumers evaluated paired beef samples according to four sensory traits, and the weighted results were combined to produce a Meat Quality score (MQ4). The consumers also categorized the beef samples to one of four grades (unsatisfactory, good everyday, better than everyday and premium). The proportion of samples assigned to each grade was similar for Japanese and Australian consumers for yakiniku and shabu shabu cooking methods; however, Japanese consumers assigned lower scores to the grill samples. In terms of the MQ4 boundary scores between grades, these were very similar for both Japanese and Australian consumers across all cooking methods. In terms of the weightings for the four sensory traits, juiciness was more important for Japanese consumers than Australian for grill and shabu shabu cooking methods. Flavor had the highest weighting for both consumer groups. This study showed that a beef description system based on the MQ4 score, with some adjustments to the weightings and cut‐off values, could be useful in describing the eating quality of beef for the Japanese consumer.